3.1 AORTIC STIFFNESS IN MIDDLE AGED WOMEN IS HERITABLE AND RELATES TO BLOOD PRESSURE AND AORTIC CALCIFICATION: A TWIN STUDY - M. Cecelja; B. Jiang; K. McNeill; M.L. Frost; T. Spector; P. Chowienczyk (Artery Research, 2009)
Background: Pulse wave velocity (PWV), measure of aortic stiffness, is predictive of cardiovascular events. PWV is strongly related to age and blood pressure but its relation to other risk factors and presence of calcification is unclear. We sought to determine the association between PWV and cardiovascular risk factors, aortic calcification and heritability of PWV. Methods: Subjects were 900 female twins (504 dizygotic, 396 monozygotic), 53–63 years (interquartile range), from TwinsUK cohort. PWV was determined over the carotid-femoral region using the SphygmoCor system. Age matched women (n=40) with PWV in the 1st and 3rd tertiles of the PWV distribution (entire cohort) underwent computed tomography from the carotid to iliac bifurcation to determine calcification. Calcium content was scored using the Agatston method. Heritability of PWV was determined using structural equation modelling. Results: In multivariate regression PWV was significantly correlated with age, mean arterial blood pressure (MAP) and heart rate (standardized regression coefficients, β=0.41, 0.39 and 0.20 respectively, each P<0.001). PWV was not significantly associated with LDL-cholesterol, HDL-cholesterol, smoking or body mass index. Aortic calcification was greater (median 450 vs. 63 units, P=0.001) in the highest compared to lowest tertile of PWV and was independently association with PWV in regression analysis (β=0.48; P<0.01). Heritability of PWV was 0.54 and when corrected for MAP and heart rate 0.51. Conclusion: In women aortic stiffness is heritable and relates to age, blood pressure and aortic calcification but not to other conventional cardiovascular risk factors. Genes involved in aortic calcification may be important determinants of PWV.